The Powdering Process with a Set of Ceramic Mills for Green Tea Promoted Catechin Extraction and the ROS Inhibition Effect - Kouki Fujioka; Takeo Iwamoto; Hidekazu Shima; Keiko Tomaru; Hideki Saito; Masaki Ohtsuka; Akihiro Yoshidome; Yuri Kawamura; Yoshinobu Manome (Molecules, 2016)
For serving green tea, there are two prominent methods: steeping the leaf or the powdered leaf (matcha style) in hot water. The purpose of the present study was to reveal chemical and functional differences before and after the powdering process of green tea leaf, since powdered green tea may contribute to expanding the functionality because of the different ingesting style. In this study, we revealed that the powdering process with a ceramic mill and stirring in hot water increased the average extracted concentration of epigallocatechin gallate (EGCG) by more than three times compared with that in leaf tea using high-performance liquid chromatography (HPLC) and liquid chromatography–tandem mass Spectrometry (LC-MS/MS) analyses. Moreover, powdered green tea has a higher inhibition effect of reactive oxygen species (ROS) production in vitro compared with the same amount of leaf tea. Our data suggest that powdered green tea might have a different function from leaf tea due to the higher catechin contents and particles.